Trends of the Epidemiology of Candidemia in Switzerland: A 15-Year FUNGINOS Survey. (17th September 2021) - Adam, Kai-Manuel; Osthoff, Michael; Lamoth, Frédéric; Conen, Anna; Erard, Véronique; Boggian, Katia; Schreiber, Peter W; Zimmerli, Stefan; Bochud, Pierre-Yves; Neofytos, Dionysios; Fleury, Mapi; Fankhauser, Hans; et al.
Abstract: Background: The increasing incidence of candidemia and emergence of drug-resistant Candida species are major concerns worldwide. Long-term surveillance studies are needed. Methods: The Fungal Infection Network of Switzerland (FUNGINOS) conducted a 15-year (2004–2018), nationwide, epidemiological study of candidemia. Hospital-based incidence of candidemia, Candida species distribution, antifungal susceptibility, and consumption were stratified in 3 periods (2004–2008, 2009–2013, 2014–2018). Population-based incidence over the period 2009–2018 derived from the Swiss Antibiotic Resistance Surveillance System (ANRESIS). Results: A total of 2273 Candida blood isolates were studied. Population and hospital-based annual incidence of candidemia increased from 2.96 to 4.20/100 000 inhabitants ( P = .022) and 0.86 to 0.99/10 000 patient-days ( P = .124), respectively. The proportion of Candida albicans decreased significantly from 60% to 53% ( P = .0023), whereas Candida glabrata increased from 18% to 27% ( P < .0001). Other non- albicans Candida species remained stable. Candida glabrata bloodstream infections occurred predominantly in the age group 18–40 and above 65 years. A higher proportional increase of C glabrata was recorded in wards (18% to 29%, P < .0001) versus intensive care units (19% to 24%, P = .22). According to Clinical and Laboratory Standards Institute, nonsusceptibility to fluconazole in C albicans was observed in 1% of isolates, and anidulafungin and micafungin nonsusceptibility was observed in 2% of C albicans and C glabrata . Fluconazole consumption, the most frequently used antifungal, remained stable, whereas use of mold-active triazoles and echinocandins increased significantly in the last decade ( P < .0001). Conclusions: Over the 15-year period, the incidence of candidemia increased. A species shift toward C glabrata was recently observed, concurring with increased consumption of mold-active triazoles. Abstract : The incidence of candidemia increased in Switzerland from 2004 to 2018. A species shift toward C glabrata was observed after 2013, now accounting for one fourth of all candidemia, concurring with increased consumption of mold-active triazoles.